High-resolution landform assemblage along a buried glacio-erosive surface in the SW Barents Sea revealed by P-Cable 3D seismic data - Bellwald, Benjamin; Planke, Sverre; Lebedeva-Ivanova, Nina; Piasecka, Emilia Daria; Andreassen, Karin (Geomorphology, 2019)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Published version available at https://doi.org/10.1016/j.geomorph.2019.01.019 . The Quaternary sedimentary record in the Arctic captures a diverse and evolving range of landscapes reflecting cli-mate changes. Here we study the geological landform assemblage of the Upper Regional Unconformity (URU) in theSW Barents Sea. The aims are (i) to characterize buried geological landforms on a meter-scale resolution, (ii) to un-derstand their link with underlying structures, and (iii) to reconstruct paleo-ice-sheet dynamics and configurations.The data consist of a high-resolution three-dimensional (3D) P-Cable seismic cube with an extent of c. 200 km2andan inline separation of 6 m. Dominant frequencies of c. 150 Hz allow to image landforms at URU with a vertical res-olution of 1–5 m and a horizontal resolution of 3–6 m. We conduct detailed horizon-picking and seismic attributeanalysis of the buried URU horizon. We identified four sets of mega-scale glacial lineations, and shear band ridgeslocated to the west of a shear margin moraine. Other characteristic features include hill-hole pairs, transverse ridges,rhombohedral ridges and depressions, iceberg ploughmarks and pockmarks. Polygonal faults below URU anddeeper faults have a strong effect on the location of structures observed on URU. Bedrock packages deformeddown to 30 m below URU and up to 5 m-high transverse ridges at URU are imprints of glacio-tectonic activity.Deformed strata below URU indicate normal faulting superimposed by glaciotectonic deformation. The four setsof mega-scale glacial lineations indicate four streaming events with thawed glacial beds, with shear band ridgesforming in the shearing zone during one of these streaming events. Hill-hole pairs and rhombohedral ridges arefrozen-bed features which indicate a polythermal regime at the base of the Barents Sea Ice Sheet during multiplestreaming phases. This study therefore shows that paleo-ice streams have been temporarily frozen to the groundin the ...